Visual Performance after a Unilateral or Bilateral Implantation of Enlarged Depth-of-Focus Intraocular Lens in Patients with Cataract: A Prospective Clinical Trial - Se Hyun Choi; Hyo kyung Lee; Chang Ho Yoon; Mee Kum Kim (Journal of Ophthalmology)
Purpose. To investigate visual performances after a unilateral or bilateral implantation of enlarged depth-of-focus intraocular lens in patients with cataract. Methods. In this prospective study, uneventful phacoemulsification and TECNIS® Symfony intraocular lens implantation were performed in 20 eyes of 17 patients. At postoperative 1, 4, and 12 weeks, the logarithm of the minimal angle of resolution visual acuity at far, intermediate, and near distances and the spherical equivalent in manifest refraction and automated refraction were measured. A questionnaire was used to investigate glare, spectacle dependency, and satisfaction at 12 weeks. The mean numerical error and mean absolute error were compared between intraocular lens formulas to assess the best-fit formula. Results. The logarithm of the minimal angle of resolution visual acuity significantly improved to 0.02 at far, 0.02 at intermediate, and 0.27 at near distances at 12 weeks (p<0.05). Spherical equivalent was −0.79 D on automated refraction and was significantly lower than −0.26 D measured on manifest refraction. Patients’ satisfaction score was 9.06, 8.94, and 6.65 for far, intermediate, and near distances, respectively. Near glasses were required in 5 patients and 2 patients complained of photic phenomenon. Visual performances were not significantly different between bilateral and unilateral implanted patients. No patients reported bilateral imbalance due to unilateral surgery. The mean numerical error was closest to 0 D using the Barrett Universal II formula. The mean absolute error was not significantly different between these formulas. Conclusion. Unilateral or bilateral implantation of the enlarged depth-of-focus intraocular lens seems to be equally effective in improving visual performances in patients with cataract.